Screening of Phytochemicals and Anticancer Potential of Maclura Pomifera Leaves Extract - Silwat Saeed, Muhammad Imran Ali Khan, Sana Ayesha, Zartasha Zahid, Muhammad Younis, Muhammad Waqas Kashan, Gul Zahra Khan, Muhammad Tahir, Sajid Abbas Khan, Muhammad Kamal, Tauqeer Mansab (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Maclura pomifera, is small deciduous tree which is commonly called as Osage orange. It typically grows about 8 to 15 meters tall. Maclura pomifera secrete white latex material which is sticky in nature on damaging. The common name of this plant is not related with citrus fruit family “orange” Maclura pomifera belongs to mulberry family called Moraceae. Method: The extract of Maclura pomifera leaves was prepared by using ethanol as a solvent. The major groups of phytochemicals were present it such as, alkaloids, tannins, saponins, flavonoids and steroids. Results: The different parts of plants contain, alkaloids, flavonoids, and polyphenolic and many other bio-compound. Due to these compounds, plants posse’s antidiabetic, anti-cardiovascular, and anticancer activities. The leaves of Maclura pomifera extract possessed higher cytotoxic potential with IC50 78.9 µg/ml. The cytotoxic potential of extract was checked through MTT assay against the hepatic cancer (HepG2) cells, Conclusion: These bio-compounds are present in the Maclura pomifera, due to this reason, this plant is used against several disorders such as diabetes, cardiovascular and cancer. Which give the valuable results. Keywords: Phytochemicals, Anticancer, Cardiovascular, Maclura pomifera, Bio-compounds, Cytotoxic potential